Entre nouveau droit de la mer et privatisation des océans : jusqu’où va le Canada dans l’Arctique ? - Sanguin, André-Louis (Études canadiennes / Canadian Studies, 2015)
The Third UN Conference on the Law of the Sea (Montego Bay, 1982) gave rise to the implementation of the new Law of the Sea (1994) which is acting as a kind of world constitution for sea and ocean spaces. Its key innovation consists in a nationalization of the sea, which assigns to coastal states a 200-mile Exclusive Economic Zone off their coastline (a 12-mile exclusive territorial sea plus a 188-mile patrimonial economic sea). With the Arctic Waters Prevention Pollution Act (2009) Canada unilaterally extended its territorial waters limit to 200 miles into the Arctic. Thus Canada very clearly becomes one of the leading countries in the race to expand its maritime boundary to high sea in the same way than Chile with its Mar Presencial concept.Within Canada’s Arctic, the Mare Clausum / Mare Liberum paradigm is at work with Canada on the one hand, and waterside or user States on the other. Canada’s Arctic is confronted with five new geopolitical challenges: the US will for control, Russia’s annexation endeavor through Lomonossov Ridge, the push for offshore oil and natural gas drills, the emergence of new indigenous territories (Greenland, Nunavut, Nunavik), the impact of shipping traffic as a result of global warming (Northwest Passage navigability). Canada sees its Arctic archipelago channels as internal waters, while the US, Russia and the EU conceive them as international waters. Beyond this political-legal contrast, a struggle is taking place for the control and share of the Arctic, which is becoming an Ice Eldorado. La Troisième Conférence des Œuvres sur le Droit de la Mer (Montego Bay, 1982) a engendré, en 1994, la mise en place d’un nouveau Droit de la Mer, sorte de constitution universelle des espaces maritimes et océaniques de la planète. Sa grande innovation consiste en une nationalisation de la mer, attribuant aux Etats côtiers une Zone Economique Exclusive de 200 milles à partir de leur littoral (12 milles de mer territoriale exclusive + 188 milles de mer patrimoniale économique). Par la Loi sur la ...